Neuropsychological aspects of brain injury litigation : a medicolegal handbook for lawyers and clinicians - Moore, Phil S., 1980-; Brifcani, Shereen, 1980-; Worthington, Andrew (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2021)
"This accessible handbook focuses on the importance of neuropsychological evidence and the role of the neuropsychologist as expert witness in brain injury litigation. This thorough, evidence-based resource fosters discussion between the legal profession and expert neuropsychological witnesses. The chapters reflect collaborations between leading personal injury lawyers and neuropsychologists in the UK. Key issues in brain injury litigation are addressed that are essential to an understanding of the role of the neuropsychologist as expert witness and of neuropsychological evidence for the courts. These include neuropsychological testing, assessment of quantum, vocational rehabilitation, mental capacity, forensic outcomes, the frontal paradox, mild TBI and more. Combining the scientific and legal background with practical tips and case examples, this book is valuable reading for legal professionals, particularly those working in personal injury and clinical negligence, as well as trainees, students and clinicians in the field of neuropsychology, neurorehabilitation and clinical psychology"--
Legal principles in litigation / Henry F Charles and Ruth Johnson -- Premorbid abilities : cognition, emotion, and behaviour / Martin Bunnage with Marc Willems -- Neuropsychological testing in brain injury litigation : a critical part of the expert neuropsychological examination / Andrew Worthington and Phil S Moore -- Paediatric outcomes after traumatic brain injury : social and forensic risk management in multidisciplinary treatment approaches / Hope Kent, James Tonks, and Huw Williams with Ian Brownhill -- Effort testing, performance validity, and the importance of context and consistency / Simon Gerhand, Chris A. Jones, and David Hacker -- Mild traumatic brain injury and persistent neuropsychological symptoms / Andrew Worthington and Phil S Moore -- The frontal lobe paradox / Sam Fisher-Hicks, Rodger Ll Wood, and Bill Braithwaite -- Assessing mental capacity in brain injury litigation / Ian Brownhill -- Legal principles of quantum / William Latimer-Sayer -- Practical applications of quantum principles / Andrew Worthington, William Latimer-Sayer, and Andy Tyerman -- Conclusion : formulating neuropsychological opinion in brain injury / Phil S. Moore, Shereen Brifcani, and Andrew Worthington.
Keywords: Personal injuries -- England -- Trial practice; Forensic neuropsychology -- England; Evidence, Expert -- England; Medical jurisprudence -- England; Brain damage -- Psychological aspects; Brain -- Wounds and injuries; Neuropsychology; PSYCHOLOGY / Neuropsychology; LAW / Medical Law & Legislation; LAW / Mental Health